Active Metabolites of Isoxazolylpenicillins in Humans - Thijssen, H. H. W. (1976)
Metabolites of the isoxazolylpenicillins that still possessed antibacterial activity were shown to be present in urine and serum. In healthy subjects, the amounts excreted in urine were low; 10 to 23% of the excreted penicillin activities represented the metabolites. The highest amount of metabolite in urine was found for oxacillin, and the lowest was found for flucloxacillin. No extreme differences in the amounts of metabolite excreted were observed when the compounds were administered orally or intravenously. In one healthy subject metabolite levels were estimated for cloxacillin in serum. Very low levels were found, i.e., about 9% of the activity. In subjects with highly impaired renal function, the metabolite may represent up to 50% of the total level of penicillin in serum. The antibacterial activities of the different metabolites were of the same order of magnitude as those of the respective parent compounds. Also, the activity against benzylpenicillin-resistant staphylococci was retained. It is not likely that the formation of the active metabolites should influence therapeutic results.